2017
DOI: 10.25181/jppt.v15i2.120
|View full text |Cite
|
Sign up to set email alerts
|

Peran Sarana Angkutan Darat Dalam Upaya Peningkatan Efisiensi Distribusi Ternak Dan Hasil Ternak Sapi Potong Di Indonesia

Abstract: In livestock trading system and cattle product such as meat and other livestock products always involves some businesses that make up the chain of marketing. Tradable commodity that can be distributed right from the producer to the end consumer in the form of live cattle or in the form of livestock product. Distribution activities of livestock and livestock products by land necessarily involves a good means of land transport trains, trucks and other means of land transport. While also involving the various lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The ownership of a vehicle represents that vehicle as an essential capital/asset for animal trading. Winarso (2015) revealed that adequate transportation facility is very urgent to prevent weight loss and deterioration in meat quality in cattle during the transportation process due to several factors: (a) fear and pain resulting in stress in cattle, (b) abdominal bloating due to cows being bound and unable to move freely, (c) dehydration due to long-distance travel without adequate watering, which can reduce weight and even cause death, and (d) fatigue. This researcher found that pick-up cars were commonly used by livestock traders in Indonesia, as found in the livestock market in Payobasuang, Payakumbuh.…”
Section: Resultsmentioning
confidence: 99%
“…The ownership of a vehicle represents that vehicle as an essential capital/asset for animal trading. Winarso (2015) revealed that adequate transportation facility is very urgent to prevent weight loss and deterioration in meat quality in cattle during the transportation process due to several factors: (a) fear and pain resulting in stress in cattle, (b) abdominal bloating due to cows being bound and unable to move freely, (c) dehydration due to long-distance travel without adequate watering, which can reduce weight and even cause death, and (d) fatigue. This researcher found that pick-up cars were commonly used by livestock traders in Indonesia, as found in the livestock market in Payobasuang, Payakumbuh.…”
Section: Resultsmentioning
confidence: 99%
“…The previous research related to the thematic logistics of livestock had been carried out by other researchers (L. V. Holdova, et al 2019, Santoso, et al 2013, and Winarso, 2001. L.V.…”
Section: Introductionmentioning
confidence: 99%
“…Santoso, et al (2013) examined the potential for developing a dairy farming business using the agribusiness paradigm. On the other hand, Winarso (2001), through his research regarding the role of land transportation facilities in increasing the efficiency of distribution of livestock and beef cattle products in Indonesia, found the fact that the use of livestock logistics transportation facilities had not been maximally implemented even though it had a potential to be developed. Some of these studies are very useful as references in assessing cattle farming.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have conducted research related to the logistics of cattle farming (LV Holdova et al, 2019;Santoso et al, 2013;Winarso, 2001). LV Holdova et al (2019) through their research examined the effect of age on the productivity and quality of milk production of dairy cows, indicating the need for livestock stock development.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Santoso et al (2013), through their research related to the potential for developing a dairy farming business, found a more optimized agribusiness paradigm. Another researcher by Winarso (2001) through his research examining the role of land transportation in increasing the efficiency of livestock distribution, found the results of a study that so far the distribution transportation pattern has not been optimized. Some of these studies are very useful for researchers as references in this study.…”
Section: Introductionmentioning
confidence: 99%